2022
DOI: 10.7717/peerj.13824
|View full text |Cite
|
Sign up to set email alerts
|

Users’ needs for a digital smoking cessation application and how to address them: A mixed-methods study

Abstract: Background Despite their increasing prevalence and potential, eHealth applications for behavior change suffer from a lack of adherence and from dropout. Advances in virtual coach technology provide new opportunities to improve this. However, these applications still do not always offer what people need. We, therefore, need a better understanding of people’s needs and how to address these, based on both actual experiences of users and their reflections on envisioned scenarios. Methods We conducted a longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…Therefore, application component usability should be a designer's priority. For future research, the suggested dataset contains user characteristics and more free-text replies [13]. Note that the experiment's findings will teach the platform to identify user habits and provide stratified users with personalized engagement suggestions using AI [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, application component usability should be a designer's priority. For future research, the suggested dataset contains user characteristics and more free-text replies [13]. Note that the experiment's findings will teach the platform to identify user habits and provide stratified users with personalized engagement suggestions using AI [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, these apps still do not meet everyone's needs. Thus, we need a deeper knowledge of people's requirements and how to meet them depending on users' real experiences and comments on envisioned situations [13].…”
Section: Healthmentioning
confidence: 99%